Before IAS 39, Now IFRS 9: New Challenges for Financial Accountants - Daniela del Pilar Rodríguez Díaz (Contabilidad y Negocios: Revista del Departamento Académico de Ciencias Administrativas, 2017)
In this paper we will resume the main differences between the application of IFRS 9 «Financial Instruments» to be imperatively implemented in Peru since the commencement of the exercise 2018 with regards to the current IAS 39 «Financial Instruments: Recognition and Measurement», focusing in the classification and measurement of financial assets. Furthermore, a practical analysis will be applied to financial instruments in the investment banking industry.